(untitled) (Journal of the College of Basic Education, 2022)
The basic starting point for this study is the intellectual value of the symbolic significance of the philosophy of nothingness and its impact on the dramatic personality, which was adopted by most of the arts and literature. The idea of ​​the nihilistic personality has attracted many philosophers, artists and writers, and they dealt with it in their literary and artistic productions. Here we try to focus in this study on one of the angles of this approach, which is the view of drama and its impact on the idea of ​​death leading to the construction of the nihilistic personality of the playwrights.